Concentrations of uremic bacterial metabolites in patients with post-COVID-19 syndrome - Brigo, Natascha; Mayr, Wolfram; Taenzer, Maja; Löffler-Ragg, Judith; Schroll, Andrea; Engl, Sabine; Schütz, Burkhard; Rappl, Peter; Heine, Till; Weiss, Günter; Kurz, Katharina (Frontiers in Cellular and Infection Microbiology, 2025)
Post-COVID-19 syndrome (PCS) is characterized by persistent symptoms and reduced mental and physical performance following the acute phase of COVID-19. The underlying mechanisms remain unclear but may involve gut microbiota dysbiosis and immune-related changes in amino acid metabolism. This pilot study aimed to investigate whether specific bacterial uremic metabolites (BUM) are altered in patients with post-infectious syndromes and whether these alterations are associated with PCS symptoms. We examined BUM in 25 PCS patients, 8 Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) patients, and 8 healthy controls (Ctrls). Concentrations of BUM were determined in second morning urine samples using mass spectrometry (Biovis Diagnostik, Limburg, Germany). Standardized questionnaires assesed physical, cognitive, psychological, and somatic symptoms and mental health status. PCS and ME/CFS patients exhibited significantly higher scores for post-exertional malaise (PEM) and somatic symptom severity compared to healthy controls (p<0.001). Elevated BUM concentrations were found in 64% of PCS patients, compared to 37.5% of both healthy controls and ME/CFS patients. While overall BUM levels did not significantly differ between groups, heatmap clustering revealed distinct metabolic patterns. Elevated tryptamine and 4-hydroxyphenylpropionic acid (HPHPA) and higher hippuric acid and trimethylamine concentrations, were exclusively analysed in patients with post-infectious syndromes. Our pilot study suggests that urine metabolomic analysis may be a useful approach for investigating the role of gut dysbiosis and BUM in patients with PCS.